Shape Stabilization of Steel Suspension Bridge - Algirdas Juozapaitis; Arnoldas Norkus; Povilas Vainiūnas (The Baltic Journal of Road and Bridge Engineering)
Stabilization of primary shape of suspension bridge is one of the governing design problems of the structure. The form, i.e. shape changes of suspension steel bridge, is prescribed more by kinematic vs elastic displacements. Kinematic displacements developed due to asymmetric loadings. Total displacements can be relatively split into kinematic and elastic components. Firstly, kinematic displacements are determined, secondly elastic displacements are evaluated taking into account the shape of cable to be changed. Such a relative splitting of displacements allow an evaluating the contribution of both total displacement components and an employing of the efficient engineering stabilization tools. The developed analytical expressions for determining of total and kinematic displacements for cable any cross are presented. The suspension bridge primary shape stabilization methods and their efficiency are analyzed. It is proposed to introduce the engineering tools for constraining horizontal displacements of suspension cable, resulting not only in reduction of vertical cable displacements, but also in stabilizing of the primary shape of the bridge.